Improved flexural behaviour of reinforced concrete beam strengthened using stainless steel wire mesh (Fracture and Structural Integrity, 2025)
The paper presents an experimental investigation of the flexural behaviour of reinforced concrete (RC) beam elements strengthened externally with stainless steel wire mesh (SSWM). SSWM has the potential to be an alternative composite material in place of Carbon Fiber Reinforced Polymer (CFRP) and Glass Fiber Reinforced Polymer (GFRP) because of advantages such as being cost-effective, having more fire-resistance and corrosion resistance, good bond behaviour with concrete, improve the strength of members, leaving minimal effects on structural aesthetics as it has less thickness and ease in availability. In the present study, SSWM has been wrapped externally over the beams having three different wrapping patterns, including fully wrapped vertical SSWM strips over the beam, partial wrapping of vertical SSWM strips in between the stirrups of the beam and partial wrapping of vertical SSWM strips above the stirrups of the beam, and control beam with no wrapping, each configuration having two test specimens. Results of experimental investigation in terms of cracking load, ultimate load, corresponding deflection, ductility, initial stiffness and energy absorption capacity of different wrapping patterns have been obtained and compared with those of control beam specimens. From the results obtained, it has been demonstrated that the fully wrapped SSWM strip wrapping pattern enhanced the flexural strength of the beam and showed the highest strength gain compared to the other wrapping patterns.
Keywords: 304 stainless steel; Shear strength; flexural strength; Reinforced concrete beams